Screening for carbapenem-resistant Enterobacteriaceae: Who, When, and How?. Issue 4 (19th May 2017) - Richter, Sandra S.; Marchaim, Dror
ABSTRACT: The global spread of carbapenem-resistant Enterobacteriaceae (CRE) has been fostered by the lack of preemptive screening of patients in healthcare facilities that could prevent patient-to-patient transmission. Outbreaks of CRE infections have led some institutions to implement rigorous screening programs, although controlled comparative data are frequently lacking. Resource limitations and uncertainty regarding the optimal approach has kept many facilities from enacting more active routine surveillance policies that could reduce the prevalence of CRE. The ideal population to target for screening, the frequency of testing, and the preferred test method are components of surveillance programs that remain open to debate. This review discusses the rationale for different screening policies in use and the performance characteristics of laboratory methods available to detect CRE carriage.